Screening of Phytochemicals as PIP5K1α Protein Inhibitors for Breast Cancer Treatment: A Bio Computational Study - Alharbi, Ahmed Mulfi (International Journal of Pharmaceutical Investigation, 2026)
Aim/Background Breast Cancer (BC) is one of the most common cancers affecting women globally. PIP5K1α catalyzes PtdIns-4,5-P2 (PIP2), a Precursor to PtdIns-3,4,5-P3 (PIP3), required for AKT activation. Overexpression of this protein in BC cells suggests that it contributes to tumor progression. Materials and Methods In the search for natural inhibitors of BC, PyRx0.8 tools were used to screen 261 compounds derived from Withania somnifera (W. somnifera) against the PIP5K1α enzyme, with ISA-2011B serving as a positive control. Results Among them, quercetin, quinic acid, and alpha-D-galactose bind strongly to PIP5K1α, with affinities comparable or superior to ISA-2011B. In addition, these compounds interacted with the key active residues (such as Asp166, Arg227, and Val235) of PIP5K1α. Furthermore, these compounds possess good druglike properties, making them a promising candidate for developing PIP5K1α inhibitors for BC treatment. Conclusion However, additional experimental validation is required to optimize these compounds as PIP5K1α inhibitors.
Keywords: Breast Cancer; PIP5K1α; Withania somnifera; Virtual Screening; Druglikeness.